The Incoherent Fluctuation of Folate Pools and Differential Regulation of Folate Enzymes Prioritize Nucleotide Supply in the Zebrafish Model Displaying Folate Deficiency-Induced Microphthalmia and Visual Defects - Hsiao, Tsun-Hsien; Lee, Gang-Hui; Chang, Yi-Sheng; Chen, Bing-Hung; Fu, Tzu-Fun (Frontiers in Cell and Developmental Biology, 2021)
Objective: Congenital eye diseases are multi-factorial and usually cannot be cured. Therefore, proper preventive strategy and understanding the pathomechanism underlying these diseases become important. Deficiency in folate, a water-soluble vitamin B, has been associated with microphthalmia, a congenital eye disease characterized by abnormally small and malformed eyes. However, the causal-link and the underlying mechanism between folate and microphthalmia remain incompletely understood. Methods: We examined the eye size, optomotor response, intracellular folate distribution and the expression of folate-requiring enzymes in zebrafish larvae displaying folate deficiency (FD) and ocular defects. Results: FD caused microphthalmia and impeded visual ability in zebrafish larvae, which were rescued by folate and dNTP supplementation. Cell cycle analysis revealed cell accumulation at S-phase and sub-G1 phase. Decreased cell proliferation and increased apoptosis were found in FD larvae during embryogenesis in a chronological manner. Lowered methylenetetrahydrofolate reductase (mthfr) expression and up-regulated methylenetetrahydrofolate dehydrogenase (NADP+-dependent)-1-like (mthfd1L) expression were found in FD larvae. Knocking-down mthfd1L expression worsened FD-induced ocular anomalies; whereas increasing mthfd1L expression provided a protective effect. 5-CH3-THF is the most sensitive folate pool, whose levels were the most significantly reduced in response to FD; whereas 10-CHO-THF levels were less affected. 5-CHO-THF is the most effective folate adduct for rescuing FD-induced microphthalmia and defective visual ability. Conclusions: FD impeded nucleotides formation, impaired cell proliferation and differentiation, caused apoptosis and interfered active vitamin A production, contributing to ocular defects. The chronological and incoherent fluctuation among folate adducts and increased expression of mthfd1L in response to FD reflect the context-dependent regulation of folate-mediated one-carbon metabolism, endowing the larvae to prioritize the essential biochemical pathways for supporting the continuous growth in response to folate depletion.